Neurocognitive Function Among Hivinfected Children On Protease Inhibitor -Based Versus Non-Protease Inhibitor Based Antiretroviral Therapy In Uganda: A Pilot Study - Nalwanga, Damalie; Musiime, Victor; Bangirana, Paul; Nishiguchi, Erika Phelps; Kiggwe, Andrew; Ssesanga, Titus; Ssenkusu, John M.; Musoke, Philippa; Cusick, Sarah E. (BMC pediatric, 2021)
HIV infection is associated with significant neurocognitive deficits making maximization of cognitive function among children receiving antiretroviral therapy (ART) a public health imperative. Non-protease inhibitors (non-PIs) achieve higher drug levels in the cerebral spinal fluid (CSF) compared to PIs, potentially leading to better neurocognitive function by reducing CSF viral load and inflammation. ART that maximises children’s neurodevelopment and school achievement could result in improved quality of life and productivity as adults, but little research to date has examined whether non-PI ART is associated with better neurocognitive outcomes. We compared the neurocognitive function between children living with HIV receiving PI-based and non PI-based ART.We recruited a consecutive sample of clinically stable Ugandan children living with HIV aged 5–12 years who received PI-based or non PI-based ART for ≥ 1 year (viral load < 1000 copies). Neurocognitive function was assessed using the Kaufman Assessment Battery for Children, the Test of Variables of Attention, and Bruininks-Oseretsky Test of Motor Proficiency. Age-adjusted neurocognitive z-scores for the two groups were compared using linear regression models in STATA version 13. The Hommel’s method was used to adjust for multiple testing.We enrolled 76 children living with HIV; 34 on PI ART and 42 on non-PI ART. Mean (±SD) age was greater in the non-PI vs. PI group (9.5 ± 1.9 vs. 8.5 ± 2.0) years (p = 0.03). Children in the non-PI group had lower socioeconomic scores (5.7 ± 3.3 vs. 7.4 ± 2.8, p = 0.02). There was no difference in neurocognitive function between the groups (adjusted p > 0.05) for KABC and TOVA. Children in the PI group had better total BOT scores than their counterparts (46.07 ± 1.40) vs. 40.51 (1.24), p = 0.03).We detected no difference in neurocognitive function among children on PI and non PI-based ART therapy based on KABC and TOVA tests. Children on PI based ART had better motor function than their counterparts. We recommend a prospective study with a larger sample size.
Keywords: Neurocognitive function; Children; HIV; ART